Pencegahan dan Penanganan Perilaku Bullying Verbal di Sekolah Dasar - Sadaruddin, Sadaruddin; Santini, Reski; Alwiah, Sitti; Sari, Siti Khadijah Cantika (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2024)
This study investigates the psychological impacts and prevention strategies of verbal bullying, focusing on its long-lasting effects on self-esteem and mental health, and its prevalence in school environments. The research aims to deepen understanding of verbal bullying dynamics, contributing factors, and effective countermeasures. Employing a mixed-methods approach, the study collects data through surveys, interviews, and observations from students and staff at UPT SPF SD Negeri Kapasa in Makassar. Quantitative analysis measures the incidence of verbal bullying, while qualitative analysis explores personal experiences and the effectiveness of an anti-bullying program implemented in the school. Results indicate a significant decrease in bullying instances and a positive shift in student behavior and awareness post-intervention, emphasizing the importance of sustained educational efforts and policy reinforcement to cultivate a respectful and empathetic school culture.